2016
DOI: 10.1021/acsami.6b06024
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Tungsten Spheres and Epoxy Composites in Three-Dimensional Graphene Foam and Its Enhanced Acoustic Performance as a Backing Material

Abstract: Backing materials play important role in enhancing the acoustic performance of an ultrasonic transducer. Most backing materials prepared by conventional methods failed to show both high acoustic impedance and attenuation, which however determine the bandwidth and axial resolution of acoustic transducer, respectively. In the present work, taking advantage of the structural feature of 3D graphene foam as a confined space for dense packing of tungsten spheres with the assistance of centrifugal force, the desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Consequently, graphene foam is a promising filler material for developing advanced multifunctional nanocomposites. Graphene foam–polymer composites have been synthesized for a wide range of potential applications, such as strain sensors, supercapacitors, electrochemical biosensors, fuel cells, electromagnetic interference shielding, , biocompatible scaffolds, , thermal interface materials, damping, and acoustic backing materials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, graphene foam is a promising filler material for developing advanced multifunctional nanocomposites. Graphene foam–polymer composites have been synthesized for a wide range of potential applications, such as strain sensors, supercapacitors, electrochemical biosensors, fuel cells, electromagnetic interference shielding, , biocompatible scaffolds, , thermal interface materials, damping, and acoustic backing materials …”
Section: Introductionmentioning
confidence: 99%
“…Graphene foam−polymer composites have been synthesized for a wide range of potential applications, such as strain sensors, 25−28 supercapacitors, 29 electrochemical biosensors, 30 fuel cells, 31 electromagnetic interference shielding, 32,33 biocompatible scaffolds, 34,35 thermal interface materials, 36 damping, 37 and acoustic backing materials. 38 This study aims to harness desirable properties of graphene foam for developing epoxy-based composites which exhibit simultaneous improvement in thermal, mechanical, and electrical properties. It has been demonstrated that the 3D interconnected network of graphene in the epoxy matrix leads to an improvement in electrical conductivity, flexural modulus, flexural strength, and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene foam has attracted attention as a highly efficient nanofiller for polymers to enhance their properties and performance . Graphene foam based polymer composites have been fabricated for a variety of applications, such as strain sensors, supercapacitors, electrochemical biosensors, biocompatible scaffolds, electromagnetic shielding, fuel cells, microwave shielding, thermal interface materials, and as acoustic backing material . These studies clearly demonstrate the potential of GrF for developing multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%
“…GrF-polymer fuselage and wing coatings would protect against extreme weather conditions such as lightning strikes and freezing rain encountered during flight due to their superior electrical and thermal conductivities. GrF-polymers are known to be shock, vibration, and noise dampening materials leading to safer and more comfortable transit [10] . Polymer composites commonly used for commercial aircraft vehicles [11] .…”
Section: Aerospacementioning
confidence: 99%
“…Centrifugal stirring, application of vacuum force, and a type of mold casting was employed to synthesize 3D GrF-tungsten-epoxy (GrF-W-Ep) composites. Qiu et al [10] used centrifugal mixing to enhance infiltration of epoxy polymer containing tungsten spheres as a secondary nanofiller into GrF's cellular structure [10] . Epoxy was placed in the bottom of a test tube to create a smooth, flat surface on which the 3D GrF was to be placed.…”
Section: Synthesis Of 3d Graphene Foam-polymer Compositesmentioning
confidence: 99%